Paleoenvironmental analysis and interpretation of upper Quaternary sequences in summit planation surfaces of center-south of Sierra de Comechingones, Córdoba, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The summit planation surfaces present in Sie- rrasPampeanas correspond to antique erosion sur- faces generated on Precambrian-Early Paleozoic crystalline basement rocks, which were faulted and tilted during the Andean (Tertiary) orogeny, and subsequently subjected to new denudative cycles. This paleosurfaces are partially covered by Cenozoic sediments (mainly of a Quaternary age), in general of loessic/loessoid origin, with average thickness of less than a meter, with the exception of some sites where they are over 5 meters. The study of these sequences, called deposits of pampas de altura (summit plains), allows mak- ing not only an approach to paleoclimatic and paleoenvironmental conditions that characterized the Sierras Pampeanas during the Quaternary, but also a comparative analysis with the surrounding low plains. There are several studies about the Quaternary record of the lowlands in the vicinity of the study region, from the pioneering work of Bodenbender (1894), Doëring (1907) and Frengüelli (1925), until the most recent contributions of Cantú and Degiovanni (1984), Blarasin and Sánchez (1987), Iriondo (1990a,b, 1994), Cantú (1992), Iriondo and Kröhling (1995), Cioccale (1999), Carignano (1999),Schiavo (2003), Cantú et al. (2004, 2006), Kemp et al. (2004a, 2006), Frechen et al. (2009), Sanabria and Argüello (2009, 2011), Tauber et al. (2012), among others. For the mountain areas, there are still few works, such as those by Montes (1958), González (1960), Manzur (1995), Córdoba et al. (2005), Tauber(2006), Tauber and Goya (2006), Tauber et al. (2008) and Krapovickas and Tauber (2012a,b).The objective of this work was to analyze the Quaternary deposits localized in the summit pla- nation surface of the Sierra de Comechingones, between 32º42´-32º50´S and 64º52´-64º59´W (Fig. 1), to establish a preliminary stratigraphic sequence for the area and to suggest the paleoenvironmental and paleoclimatic conditions during sedimentation.The Comechingones ranges, as part of the Sierras Pampeanas, shows classic asymmetrical transverse profiles (Fig. 2). The western side is a fault scarp of high gradient, whose displacement (variable between 200 and 1000 m) decreases toward the South, while the eastern side is a gentle structural slope, with well defined steps, associated to tectonism and/or differential erosion (Fig. 2, A-A´ and B-B´ profiles).In the mountain area, the dominant lithological types are gneissic-migmatitic rocks (the Monte Gua- zú Complex), mylonites and ultramylonites (the Guacha Corral Shear Zone), and granitic rocks (the Cerro Áspero batholith). The Quaternary deposits are exposed mainly in the piedmont plains, and, in a lesser extent in the mountain valleys covering the plains developed at the summit areas of the ranges.The landscape of the study area shows three major morphoestructural features: 1) submeridianmegablocks of Precambrian-lower Paleozoic, crys- taline rocks, 2) a western scarp associated to the Comechingones fault (Gordillo y Lencinas, 1979; Introcaso et al. 1987, Costa, 1996), and 3) a lower eastern structural slope, highly dissected by the drainage network after the Andean movements, which preserve relicts of erosion paleosurfaces (Stelzner, 1885; Rovereto, 1911; Penck, 1914, 1920;Rassmuss, 1916; Schmieder, 1921; Rimann, 1926; González Díaz, 1981; Jordan et al., 1989; Costa et al., 1999; Carignano et al., 1999; Rabassa et al., 2010; Degiovanni y Andreazzini, 2013) in the summit areas (Figs. 1, 3).The study included geological and geomorpho- logical recognition, both by remote sensing andfield work. Three representative sedimentological- pedological profiles were described and interpreted (P1, P2 and P3, Figs. 4, 5), while various samples were collected. Chronology (C14 and OSL), granulometry, mineralogy of the clay fraction and organic matter content determinations were made.In the analyzed succession three main stratig- raphic units were recognized (Figs. 5, 7). Unit I is formed by light brown (7,5YR 6/4), silty loam materials, with moderately sorting. This unit is mainly massive or shows a very weak lamination. OSL dating of quartz of a sample from unit I yielded an age of 23,0 ± 2,25 ky (Fig. 5b). By means of a sharp contact there is unit II, composed by clay loam materials of light brown color (10YR 6,5/4) at the base to dark brown color (7,5YR 4/2) towards the top. This unit presents trough cross-laminated beds and cut and fill structures (Figs. 5a-d, 7) associated with small channels (Fig. 5c).The top of unit II shows a well-developed paleosol, where several horizons were recognized: 2Bt1, 2Bt2, 2Btk1, 3Btk2, 3BCkm and 4BC (Fig. 6). The diagnostic laboratory and field characteristics are detailed in Table 1 and the figure 8 represents the X-ray diffractograms of samples from the paleosol. On top of unit II and filling cracks which cut the underlying units I and II, there are discontinuous and slightly laminated calcrete deposits. The thick- ness of these deposits ranges between 1 and 10 cm, and shows lateral variations in their distribution and preservation. Microscopically the calcrete shows a porphiric distribution, and is formed by a micritic mass that include loessoid material (Fig. 9). A radiocarbon age 4.180 ± 80 yr BP was determined in this calcrete. The calibration informed by the laboratory was performed using the CALIB 6.0.1 program, in conjunction with the recommendations of Stuiver and Reimer (1993). According to the calibration curve, the event of carbonation is limited between 4.529 and 4.814 years AP.Above unit II, or above the calcrete level when it is present, and through an erosional sharp contact there is unit III. It is a silty clay loam, with dark gray (10YR 4/1) and dark grayish brown (10YR 4/2) color and 0.3 to 0.4 m of thickness (Figs. 5, 7). These sediments are partially modified by pedogenesis, showing two horizons, A and AB (Fig. 6, Table 1).Unit I is interpreted as a loessic deposit, un- disturbed or with minimum local reworking, sedi- mented under arid and cold conditions. Accordingto the obtained OSL age the loess was accumulated during the late Pleistocene, then corresponding to the Last Glacial Maximum (ISO2). The above alluvial levels of unit II indicate higher water availability and sporadic occurrence of torrential erosive channeled flows, which locally removed the underlying loessic materials and deposited them in subaqueous low energy environments. Unit II would represent the transition to more benign conditions of the Hypsithermal period (Late Pleistocene-Early Holocene), whose climax is here linked to the recognized paleosol on top of unit II. The pedogenetic characteristics of this paleosol would indicate warm and wet conditions (higher than at present), and an environment of meadows with grassland of high cover. This condition favored both formation and traslocation of clay and iron oxides in the soil profile, and the accumulation of high contents of organic material, all features observed in the paleosol. The formation of an erosive surface with decapitation of the paleosol, and the presence of calcretes on different profile discontinuities (textural, desiccation cracks), are associated to the Mid-Late Holocene more arid cycle, that ends with the deposition of the aeolianloessic material of unit III.Under the present temperate-wet Atlantic climatic conditions, the environment of tall grasslands was restored, the landscape stabilized, and a new pedogenesis cycle started which affected unit III and the underlying paleosol.
Keywords: loess, Late Quaternary, stratigraphy, paleoenvironment, summit planation surface, Sierra de Comechingones.